Methods of Lean Production to Improve Quality in Manufacturing - Pech, Martin; Vaněček, Drahoš (Technická univerzita v Košiciach, 2018)
Purpose: Quality in manufacturing can be improved by using lean production methods. The paper discusses traditional and modern methods of lean production and their use in different enterprises. Methodology/Approach: Through a questionnaire survey and research, 90 industrial enterprises were classified by the size, production scope and their ownership. The research results were analyzed by means of statistical methods to determine the differences in the use of lean production methods. Findings: Regarding the lean production and its different methods, the size of the enterprise is an important factor. The statistics revealed that large enterprises tend to use lean production more. It was also proved that some methods of lean production are not completely common in the Czech Republic. Moreover, some methods are quite new to the majority of the enterprises. Research Limitation/implication: Some questionnaire surveys conducted in different countries (especially in the US) use a different enterprise size classification. As the research results show, there is still a large potential for the introduction of lean production methods in small and middle-sized enterprises that can help enterprises to improve the quality of their production. Originality/Value of paper: The application of lean production methods has been investigated so far, especially in large engineering enterprises. The paper deals with the use of these methods also in small and medium sized enterprises. The authors focused their research also on non-engeneering enterprises in the field of the food industry and production of products for domestic use too.
Keywords: lean production; lean production methods; size of the enterprise; quality of production